Mechatronics for safety, security and dependability in a new era - Arai, Eiji; Arai, Tatsuo (Elsevier, 2007)
Mechatronics for Safety, Security and Dependability in the New Era contains selected leading papers from the International Conference on Machine Automation 2004, the work of researchers from USA, Japan, China and Europe. The topics covered include: manufacturing systems such as CAD/CAM, machining and, human factors in manufacturing; robotics in relation to sensors and actuators, new control technology and, measuring and monitoring; the application of new technologies in connection with wireless communication, human behavior analysis and welfare. Mechatronics has been rapidly developing as an important area that affects all areas of society from industrial robots, automobiles, electrical appliances, computers and consumer goods etc. It also plays a role in safety recovery, such as for rescue tasks after disasters, destruction of hazardous and abandoned weapons and the restoration of polluted environments. The increasing need for safe, secure and dependable technology means that the advancement of mechatronics plays an essential role in the development of products and systems. This book provides an insight into developments in essential new methodologies and tools to design and to build machines to achieve this.